STRATEGI POLITIK PASANGAN SUKANDAR-HAMDI DALAM PEMENANGAN PEMILUKADA ULANG KABUPATEN TEBO - Joko Setyoko; Hendro Waluyo (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2021)
The phenomenal victory of the Sukandar-Hamdi pair in the re-election of Tebo district, in fact, cannot be separated from the expertise of a political strategy actor, both in reading opportunities in political momentum and reading trends in voter behavior in the Tebo area. This research was conducted in Tebo Regency, Jambi. The location which became the research location was chosen purposively (intentionally), namely in Tebo Regency, Jambi Province. Because the phenomenon of the Pemilukada in Tebo district which is the only regional head election in Jambi Province whose implementation is repeated, due to demands from the opposing parties participating in the other post-conflict local elections. This research method is a qualitative method. The results of this study found that the political strategy used by the Sukandar-Hamdi pair in winning the post-conflict local election in Tebo Regency was to form a success team or team consisting of community leaders, women, and witnesses at TPS, holding outreach to kecamtan and villages in Tebo Regency. , conducting campaigns by making a vision and mission and bringing in artists in open campaigns, using the mistakes of opponents that have been decided in the Constitutional Court to influence voters, inviting survey institutions to conduct political research